2017
DOI: 10.1080/13696998.2017.1377718
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness of osimertinib in the UK for advanced EGFR-T790M non-small cell lung cancer

Abstract: Osimertinib may be considered a cost-effective treatment option compared with PDC in the second-line setting in patients with EGFR-T790M mutation-positive NSCLC from a UK payer perspective. Further data from the ongoing AURA clinical trial program will reduce the inherent uncertainty in the analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 18 publications
1
22
0
4
Order By: Relevance
“…inhibitors for first-line treatment of NSCLC patients with EGFR mutations [42,43] or ALK translocations [44]. However, the present study had several limitations due to data availability and assumptions made at the time of the analysis.…”
Section: Discussionmentioning
confidence: 96%
“…inhibitors for first-line treatment of NSCLC patients with EGFR mutations [42,43] or ALK translocations [44]. However, the present study had several limitations due to data availability and assumptions made at the time of the analysis.…”
Section: Discussionmentioning
confidence: 96%
“…Given that the clinical evidence on the first‐line use of osimertinib is relatively new, its cost‐effectiveness evidence is rather limited. There are only two published economic evaluations for osimertinib, both conducted in second‐line settings . A model‐based cost utility analysis was conducted in the U.K. to compare the second‐line use of osimertinib with platinum‐based doublet chemotherapy in treating patients with advanced NSCLC with EGFR‐T790 M mutation over a 15‐year time horizon .…”
Section: Discussionmentioning
confidence: 99%
“…There are only two published economic evaluations for osimertinib, both conducted in second‐line settings . A model‐based cost utility analysis was conducted in the U.K. to compare the second‐line use of osimertinib with platinum‐based doublet chemotherapy in treating patients with advanced NSCLC with EGFR‐T790 M mutation over a 15‐year time horizon . This study used phase II AURA trials as the main source for clinical inputs and found that the QALY gain was 1.541 at an incremental cost of £64,283, with the ICER of £41,705.…”
Section: Discussionmentioning
confidence: 99%
“…We used the 2018 US wholesale acquisition cost (WAC) of osimertinib for a 30-day prescription, which was $14,616 12 . The corresponding price point was £5,770 in the UK and CA$8,974 in Canada 13,14 . The 2018 average exchange rates coefficients were 0.78 from the USD to the GBP and 1.30 from USD to CAD conversion 7 .…”
Section: Model Inputsmentioning
confidence: 99%